2006
DOI: 10.1248/bpb.29.1886
|View full text |Cite
|
Sign up to set email alerts
|

Effective Blood Concentration of Micafungin for Pulmonary Aspergillosis

Abstract: We previously reported that a 150 mg or higher daily dose is necessary for treatment of pulmonary aspergillosis with micafungin (MCFG) alone in patients with blood diseases. Since a delay in the treatment of pulmonary aspergillosis has a major influence on patient survival, clarification of the effective blood concentration of MCFG enables rapid treatment. Establishment of an appropriate dose is also useful for reducing the risk of adverse effects, such as MCFG-induced impairment of liver function. Aiming for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Therefore, preventive or preemptive treatments against fungal infections are needed for LDLT-recipients. 14) Several reports have demonstrated that MCFG is a safe and effective antifungal agent, 9,[15][16][17] suggesting that dose adjustment is not required for elderly patients or patients with moderate liver dysfunction or severe kidney dysfunction. 9,12) However, information on the efficacy and safety of MCFG for the treatment of fungal infections in LDLT-recipients has been limited due to the small sample sizes of the studies reported previously [18][19][20] ; i.e., less than 9 LDLT-recipients in each study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, preventive or preemptive treatments against fungal infections are needed for LDLT-recipients. 14) Several reports have demonstrated that MCFG is a safe and effective antifungal agent, 9,[15][16][17] suggesting that dose adjustment is not required for elderly patients or patients with moderate liver dysfunction or severe kidney dysfunction. 9,12) However, information on the efficacy and safety of MCFG for the treatment of fungal infections in LDLT-recipients has been limited due to the small sample sizes of the studies reported previously [18][19][20] ; i.e., less than 9 LDLT-recipients in each study.…”
Section: Discussionmentioning
confidence: 99%
“…15) On the other hand, Kishino et al demonstrated that a therapeutic drug level can be achieved by prophylactic administration of MCFG at a dose of 40-50 mg/d.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical study in Japan, the C max values of MCFG were 14.30 g/mL (single administration of 150 mg) and 2.52 g/mL (single administration of 25 mg) [19]. Shimoeda et al recommended 5.0 g/mL or higher as a target blood trough level of MCFG in establishing a dose for treating aspergillosis in patients with blood diseases [20]. The sensitivity of our method was considered satisfactory for clinical application.…”
Section: Resultsmentioning
confidence: 99%
“…However, Shimoeda et al. compared the MCFG Cmin in patients grouped according to the response of pulmonary aspergillosis based on their original criteria. The mean MCFG Cmin level was higher in patients with “marked improvement” compared to those with “improvement” (5.23 μg/mL vs. 4.08 μg/mL), although the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%